Frequent gene flow blurred taxonomic boundaries of sections in Lilium L. (Liliaceae) - Gong, Xun; Hung, Kuo-Hsiang; Ting, Yu-Wei; Hsu, Tsai-Wen; Malikova, Lenka; Tran, Huyen Trang; Huang, Chao-Li; Liu, Shih-Hui; Chiang, Tzen-Yuh (PloS one, 2017)
Gene flow between species may last a long time in plants. Reticulation inevitably causes difficulties in phylogenetic reconstruction. In this study, we looked into the genetic divergence and phylogeny of 20 Lilium species based on multilocus analyses of 8 genes of chloroplast DNA (cpDNA), the internally transcribed nuclear ribosomal DNA (nrITS) spacer and 20 loci extracted from the expressed sequence tag (EST) libraries of L. longiflorum Thunb. and L. formosanum Wallace. The phylogeny based on the combined data of the maternally inherited cpDNA and nrITS was largely consistent with the taxonomy of Lilium sections. This phylogeny was deemed the hypothetical species tree and uncovered three groups, i.e., Cluster A consisting of 4 taxa from the sections Pseudolirium and Liriotypus, Cluster B consisting of the 4 taxa from the sections Leucolirion, Archelirion and Daurolirion, and Cluster C comprising 10 taxa mostly from the sections Martagon and Sinomartagon. In contrast, systematic inconsistency occurred across the EST loci, with up to 19 genes (95%) displaying tree topologies deviating from the hypothetical species tree. The phylogenetic incongruence was likely attributable to the frequent genetic exchanges between species/sections, as indicated by the high levels of genetic recombination and the IMa analyses with the EST loci. Nevertheless, multilocus analysis could provide complementary information among the loci on the species split and the extent of gene flow between the species. In conclusion, this study not only detected frequent gene flow among Lilium sections that resulted in phylogenetic incongruence but also reconstructed a hypothetical species tree that gave insights into the nature of the complex relationships among Lilium species.
Keywords: tok genů; Phylogeny; rostlinné geny; Gene Flow; Lilium; fylogeneze; DNA chloroplastová; Genes, Plant; lilie; DNA, Chloroplast